Los chicos del ferrocarril - Nesbit, E. (Edith), 1858-1924; Sánchez-Andrade, Cristina, 1968-; Nesbit, E. (Edith), 1858-1924. (Madrid : Siruela, 2015)
When their father is taken away, three children move to the country, where they stay busy saving the train from accidents, befriending a nice old gentleman, and trying not to quarrel.
Online resource; title from ePub title page (Digitalia, viewed April 21, 2017)
Keywords: Brothers and sisters -- England -- Juvenile fiction; Children -- England -- Juvenile fiction; Country life -- England -- Juvenile fiction; Railroad stories; Electronic books